A participação política das mulheres na Câmara Municipal de Aparecida de Goiânia-GO (1967-2012) - Alves, Valdenir Maria Soares Pereira (2016)
This research analyzes the participation of aparecidenses women in the electoral process for the Aparecida Legislature of Goiânia-GO, 1967-2012 period. Identifies the causes that lead them to have little representation in the legislature Aparecidense Power and investigates whether by political parties which determines the legislation with regard to quotas, and if there are resources available to the candidates, in equality with the candidates. It is the perspective of gender studies is reflected on norms, values and concepts established through roles for men and women. It emphasizes the need for more evidence on participation and women s power of representation in the political municipality. The methodology used was bibliographical and field, based on questionnaires and interviews, and documents held in archives of the City of Aparecida de Goiania, GO.